Whole genome sequencing of Caribbean Hispanic families with late‐onset Alzheimer's disease. Issue 4 (13th March 2018) - Vardarajan, Badri N.; Barral, Sandra; Jaworski, James; Beecham, Gary W.; Blue, Elizabeth; Tosto, Giuseppe; Reyes‐Dumeyer, Dolly; Medrano, Martin; Lantigua, Rafael; Naj, Adam; Thornton, Timothy; DeStefano, Anita; et al.
Abstract: Objective: To identify rare causal variants underlying known loci that segregate with late‐onset Alzheimer's disease (LOAD) in multiplex families. Methods: We analyzed whole genome sequences (WGS) from 351 members of 67 Caribbean Hispanic (CH) families from Dominican Republic and New York multiply affected by LOAD. Members of 67 CH and additional 47 Caucasian families underwent WGS as a part of the Alzheimer's Disease Sequencing Project (ADSP). All members of 67 CH families, an additional 48 CH families and an independent CH case‐control cohort were subsequently genotyped for validation. Patients met criteria for LOAD, and controls were determined to be dementia free. We investigated rare variants segregating within families and gene‐based associations with disease within LOAD GWAS loci. Results: A variant in AKAP9, p.R434W, segregated significantly with LOAD in two large families (OR = 5.77, 95% CI: 1.07–30.9, P = 0.041). In addition, missense mutations in MYRF and ASRGL1 under previously reported linkage peaks at 7q14.3 and 11q12.3 segregated completely in one family and in follow‐up genotyping both were nominally significant ( P < 0.05). We also identified rare variants in a number of genes associated with LOAD in prior genome wide association studies, including CR1 ( P = 0.049), BIN1 ( P = 0.0098) and SLC24A4 ( P = 0.040). Conclusions and Relevance: Rare variants in multiple genes influence the risk of LOAD disease in multiplex families. These results suggest that rare variants may underlie loci identified in genome wide association studies.